The psychological explanation of religious experience - Argyle, Michael (Psyke & Logos, 2023)
The article presents a number of empirical studies in the psychology of religion. How often is religious experiences found in surveys? To what extent can religious experience be influenced by drugs? What is the psychological content of religious experience, and what effects does it have on the personal life of the individual involved?